Perancangan Ulang Rumah Sakit Ibu Dan Anak Melinda Bandung Dengan Pendekatan Psikologi Ruang - Salsabila, Dita; Faza Surya Rusyda, Hana; Sri Ismiranti, Athifa (eProceedings of Art & Design, 2024)
The public's perspective on hospitals is often associated with a negative atmosphere, such as being frightening, making it important to change this image to support both psychological and physical healing processes. The goal of the redesign of the Melinda Mother and Child Hospital in Bandung is to create an environment that caters to the psychological needs and comfort of users, particularly the people of Bandung, while they are at the hospital. The design process involved methods such as observation, interviews, questionnaires, documentation, and literature review. The hospital was redesigned using a spatial psychology approach, with the theme "Health Warm Family with Meaningfulness" supported by the concept of salutogenesis, aiming to create psychological comfort through environmental psychology. It is hoped that this redesign will have a positive effect on users, speeding up the healing process and improving health, especially from a psychological perspective. Keywords: health warm family with meaningfulness; spatial psychology; hospital; Melinda Mother and Child Hospital Bandung; salutogenesis.